1, 3‐Bis(tricyanoborane)imidazoline‐2‐ylidenate Anion—A Ditopic Dianionic N‐Heterocyclic Carbene Ligand. Issue 33 (7th June 2021) - Zapf, Ludwig; Radius, Udo; Finze, Maik
Abstract: The 1, 3‐bis(tricyanoborane)imidazolate anion 1 was obtained in high yield from lithium imidazolate and B(CN)3 −pyridine adduct. Anion 1 is chemically very robust and thus allowed the isolation of the corresponding H5 O2 + salt. Furthermore, monoanion 1 served as starting species for the novel dianionic N‐heterocyclic carbene (NHC), 1, 3‐bis(tricyanoborane)imidazoline‐2‐ylidenate anion 3 that acts as ditopic ligand via the carbene center and the cyano groups at boron. First reactions of this new NHC 3 with methyl iodide, elemental selenium, and [Ni(CO)4 ] led to the methylated imidazolate ion 4, the dianionic selenium adduct 5, and the dianionic nickel tricarbonyl complex 6 . These NHC derivatives provide a first insight into the electronic and steric properties of the dianionic NHC 3 . Especially the combination of properties, such as double negative charge, different coordination sites, large buried volume and good σ‐donor and π‐acceptor ability, make NHC 3 a unique and promising ligand and building block. Abstract : Unprecedentedly stable salts of the 1, 3‐bis(tricyanoborane)imidazolate ion with different types of counterions were obtained on large scale. Deprotonation of the imidazolate ion provided access to the corresponding dianionic NHC that acts as ditopic ligand.